Towards a cloud model choice evaluation: comparison between cost/features and ontology-based analysis. (17th March 2023) - Cantiello, Pasquale; Martino, Beniamino Di; Mastroianni, Michele; Cante, Luigi Colucci; Graziano, Mariangela
In academic institutions, there is frequently the need to provide new services, in a cloud model, to be used either in teaching or in research activities. One of the main decisions to be addressed is related to the cloud model to adopt (private, public or hybrid), and what mixing of functionalities to use for the hybrid one. In this paper two different methodologies (cost/features and semantic-based) are been experimented in order to identify the best suited cloud model to adopt for a specific problem. The long-term perspective is to build a methodology to serve as a tool to be used as decision support for the ICT manager in order to help him in this decision. The comparison between the two different methodologies shows the strengths and weaknesses of both approaches.